Vision System for Item Recognition: Case Study Computer Peripherals - Yap, Choi Sen; Ong, Tun Jie (INTI International University, 2019)
Vision System is part of Artificial Intelligence (AI) using the camera as a primary input. Over the past fifty years, the development of AI had achieved a great achievement such as the development of a Vision System. Implementation of the Vision System is not limited to industry but also as a solution to recognize an unknown object in various area. However, the availability of the current Vision System for personal usage is still limited in the market (such as Google Lens and CamFind) which is known to have a harsh requirement to whom able to use it or had limited functionality that result of unable to provide more information on the unrecognized item. Therefore, this research is proposed to create an alternate Vision System which enhancing user experience on the computer peripherals. A forum-like social environment is also develop as extra channel for the user to share information. The user will able to use this item recognition function to identify the computer peripherals that they are interested to find out and post their doubts to the forum in getting help from others.